Filamentous Bacteriophage—A Powerful Carrier for Glioma Therapy - Wang, Yicun; Sheng, Jiyao; Chai, Jin; Zhu, Cuilin; Li, Xin; Yang, Wei; Cui, Ranji; Ge, Tongtong (Frontiers in Immunology, 2021)
Glioma is a life-threatening malignant tumor. Resistance to traditional treatments and tumor recurrence present major challenges in treating and managing this disease, consequently, new therapeutic strategies must be developed. Crossing the blood-brain barrier is another challenge for most drug vectors and therapy medications. Filamentous bacteriophage can enter the brain across the BBB, compared to traditional drug vectors, phage-based drugs offer thermodynamic stability, biocompatibility, homogeneity, high carrying capacity, self-assembly, scalability, and low toxicity. Tumor-targeting peptides from phage library and phages displaying targeting peptides are ideal drug delivery agents. This review summarized recent studies on phage-based glioma therapy and shed light on the developing therapeutics phage in the personalized treatment of glioma.